Causes and Frequencies of Reoperations After Endoprosthetic Reconstructions for Extremity Tumor Surgery: A Systematic Review - Thornley, Patrick; Vicente, Matias; MacDonald, Austin; Evaniew, Nathan; Ghert, Michelle; Velez, Roberto (Clinical orthopaedics and related research, 2019)
Excision of bone tumors and endoprosthetic reconstruction allow patients early weightbearing and a potential functional advantage compared with amputation. These reconstructions do not restore the limb to normal status, however, and patients are subject to complications that may result in revision or loss of the limb. Because better understanding of these complications based on current information might help the patient and surgeon in decision-making, we undertook a systematic review of studies published on this topic. (1) What are the primary modes and proportion of failure of tumor endoprostheses in patients undergoing reconstruction after excision of primary extremity bone sarcomas? We systematically searched MEDLINE, Embase, and the Cochrane Library for all studies published from April 15, 1998, to April 15, 2018. Three reviewers independently reviewed studies reporting endoprosthetic reconstruction survival and events requiring revision for primary extremity bone tumors treated with endoprosthetic reconstruction for inclusion and performed independent data extraction. We excluded all studies with fewer than five patients, any systematic review/meta-analyses, and any study not reporting on primary extremity bone tumors. All discrepancies were resolved by the study's senior author. Data extracted from included studies were any reoperation event for wound dehiscence, any operative fixation for a pathologic fracture, and any revision of the primary endoprosthesis for implant wear or breakage, deep infection not amenable to prosthesis retention, or for local recurrence. We assessed the overall quality of the evidence with the Methodological Index for Non-Randomized Studies (MINORS) approach with a higher MINORS score representative of a more methodologically rigorous study with a total possible score of 16 points for noncomparative and 24 points for comparative studies. Forty-nine studies met criteria for inclusion from an initial search return of 904 studies, of which no studies were randomized controlled trials. From a total patient population of 2721, there was a mean followup of 93 months (range, 1-516 months) with loss to followup or death occurring in 447 of 2118 (21%) patients with six studies not providing loss to followup data. The mean MINORS score was 14 for prospective studies and 11 for retrospective studies. Overall, there were 1283 reoperations among the 2721 (47%) patients. Reoperation for mechanical endoprosthetic events (soft tissue dehiscence or periarticular soft tissue instability, aseptic loosening, or implant wear/fracture) occurred in 907 of 2721 (33%) patients. Aseptic loosening occurred at a mean of 75 months (range, 1-376 months) in 212 of 315 patients (67%). Deep infection requiring removal of the initial prosthesis occurred in 247 of 2721 (9%) patients with deep infection occurring at a mean of 24 months (range, 1-372 months) in the 190 infections (77%) with time to infection data available. Local recurrence rates requiring revision or amputation occurred in 129 (5%) of all patients. There was an overall primary endoprosthesis survival rate without any surgical reintervention of 63% among reporting studies at a mean of 79 months followup. Failures of endoprosthetic reconstructions after extremity tumor surgery are common, most often resulting from implant wear or fracture, aseptic loosening, and infection. Importantly, the aggregated data are the first to attempt to quantify the time to specific complication types within this patient population. Deep infection not amenable to endoprosthesis retention appears to occur approximately 2 years postoperatively in most patients, with aseptic loosening occurring most commonly at 75 months. Although endoprosthetic reconstruction is one of the most common forms of reconstruction after bone tumor resection, the quality of published evidence regarding this procedure is of low quality with high loss to followup and data quality limiting interstudy analysis. The quality of the evidence is low with high loss to followup and inconsistent reporting of times to reintervention events. Although the most common modes of endoprosthetic failure in this population are well known, creation of quality prospective, collaborative databases would assist in clarifying and informing important elements of the followup process for these patients. Level IV, therapeutic study.